Houlik-Ritchey, Emily. 2023. Imagining Iberia in English and Castilian Medieval Romance. Ann Arbor: University of Michigan Press. Pp. xi + 237. ISBN 9780472133352. - Piercy, Hannah (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Houlik-Ritchey, Emily. 2023. Imagining Iberia in English and Castilian Medieval Romance. Ann Arbor: University of Michigan Press. Pp. xi + 237. ISBN 9780472133352.